2000
DOI: 10.1007/s001040050026
|View full text |Cite
|
Sign up to set email alerts
|

Laparoskopisches gastric banding

Abstract: The introduction of laparoscopic gastric banding appears to have revolutionized bariatric surgery. This review presents this new method in terms of indications, operative technique and preliminary results according to our own experience as well as reports in the literature. It seems that a long-term weight reduction of more than 50% excess weight can be achieved with a low morbidity rate. In the near future laparoscopic gastric banding can possibly become the procedure of choice for the treatment of morbid obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 11 publications
1
11
0
1
Order By: Relevance
“…The technique of proper implantation of SAGB by laparoscopy has been described in detail elsewhere [15]. In summary, CO 2 pneumoperitoneum is installed after inserting the Veress needle into the left hypochondrium.…”
Section: Implantation Of Sagbmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique of proper implantation of SAGB by laparoscopy has been described in detail elsewhere [15]. In summary, CO 2 pneumoperitoneum is installed after inserting the Veress needle into the left hypochondrium.…”
Section: Implantation Of Sagbmentioning
confidence: 99%
“…A month after surgery, inflation of SAGB was commenced by injecting 3 or 4 ml of a radiology contrast medium (Iopamiro isotonic 200 mg IO; Bracco, Milan, Italy) under aseptic conditions in an out- [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Of the 190 patients who underwent SAGB, 184 (97%) could be followed up (mean, 39.4 ± 18.4 months; duration of follow-up, 6-72 months).…”
Section: Postoperative Follow-upmentioning
confidence: 99%
“…Recently, several series of patients having undergone laparoscopic gastric banding have been published. The early results in most European and Australian reports have generally been relatively good, with a low perioperative morbidity, a very low mortality, and a satisfying average excess weight loss [2,8,11,15,16,17,20,25,27,30]. Others have reported less favorable results with insufficient weight loss and/or high long-term complications rates [9,31].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the demand for bariatric surgery, the only efficient treatment for morbid obesity currently available, is rapidly expanding. Whereas Roux-en-Y gastric bypass remains the gold standard, and despite the fact that the method is relatively new, many authors consider laparoscopic gastric banding as the treatment of choice for morbidly obese patients [2,11,13,15,17,18,20,30]. Others consider gastric banding as an inappropriate method because it yields insufficient weight loss or because it is associated with an exceedingly high rate of complications [9,31].…”
mentioning
confidence: 99%
“…The failure rate in this group is reported as 10%. Klaiber et al reported the failure rate in their patients with the SAGB system as only 3.9% [50]. Because the band system is adjustable, the stoma can be adjusted in a female patient to assure a normal pregnancy if this occurs [71].…”
Section: Quality Of Lifementioning
confidence: 99%